Holography-guided procedural planning for modifying Venus P-valve implantation technique in patients with left pulmonary artery stents: a case-series - d’Aiello, Angelo Fabio; Schianchi, Laura; Bevilacqua, Francesca; Ferrero, Paolo; Micheletti, Angelo; Negura, Diana Gabriela; Pasqualin, Giulia; Chessa, Massimo (Frontiers in Cardiovascular Medicine, 2024)
Background Venus P-valve™ (Venus Medtech, Hangzhou, China) is a self-expandable bioprosthetic valve that can be transcatheter-implanted in native right ventricular outflow tract (RVOT) patients. Valve implantation is technically challenging. Due to the implantation technique, left pulmonary artery (LPA) stents represent a relative contraindication to Venus P-valve. In this case series, we describe our experience in implanting Venus P-valve in patients with previous LPA stents and the use of holographic models to facilitate procedural planning. Methods and results From January to October 2023, 17 patients were scheduled for Venus P-Valve implantation. 16/17 (94%) patients were successfully implanted. 3/16 (18.7%) patients underwent Venus P-valve implantation with LPA stents. All patients underwent pre-operative CT scan. CT data set were employed to create three-dimensional (3D) holographic models (Artiness, Milan, Italy) of the entire heart, which were useful to plan valve implantation with a modified technique. Procedural success rate was 100%. No procedural complications occurred. All three patients presented good haemodynamic and angiographic results at discharge and follow-up visits. Conclusion This case-series underscores the feasibility of Venus P-valve implantation in patients with previous LPA stents. The use of holographic models facilitated procedural planning in these challenging anatomical scenarios.